2018
DOI: 10.1002/app.46491
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing treatment on the structure and properties of poly(4‐methyl‐1‐pentene)‐based films and membranes

Abstract: The poly(4‐methyl‐1‐pentene) casting films were prepared by melt extrusion and annealed below the melting temperature. The effect of annealing conditions on the structure and properties of casting films and stretched membranes was discussed. In this work, a new peak around annealing temperature, as shown in melting curves, revealed the increase in thickness of lamellar structure. Annealing treatment led to improvements of amorphous thickness and crystal orientation. And the thickness of crystal phase correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It can be found that f H was 0.49 and the crystallinity was 0.38 in P4MP1‐ref, and they were enlarged to 0.52 and 0.40, respectively, when T h was 150°C. As shown in Figure 2, no additional melting peak arose, so the increase of f H and the crystallinity was probably caused by the lamellae perfection and molecular chains rearrangement in the amorphous phase 25,41,42 . As T h was higher than 223°C and lower than 234°C, part of the previously existed crystals was melted.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…It can be found that f H was 0.49 and the crystallinity was 0.38 in P4MP1‐ref, and they were enlarged to 0.52 and 0.40, respectively, when T h was 150°C. As shown in Figure 2, no additional melting peak arose, so the increase of f H and the crystallinity was probably caused by the lamellae perfection and molecular chains rearrangement in the amorphous phase 25,41,42 . As T h was higher than 223°C and lower than 234°C, part of the previously existed crystals was melted.…”
Section: Resultsmentioning
confidence: 94%
“…For the P4MP1 precursor film, the optimum annealing temperature and time were 205°C and 20 min, and the best cold and hot stretching temperatures were 70 and 180°C 23 . In the later work by Yin et al, 24–26 P4MP1 precursor film with different draw ratios was obtained and the optimum annealing parameters and stretching parameters were discussed. It was found that the crystallinity of the precursor film declines with increasing draw ratios.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations